COMPETITION CONTRIBUTES TO PERFORMANCE IN THE BANKING INDUSTRY LITERATURE STUDY - Sarirati, Putri; Madiistriyatno, Haries (Dinasti Publisher, 2021)
The purpose of this research is to find out the trend of research in the field of competition in the banking industry, the synthesis of competition theory and stability theory. The study used bibliometric analysis and used Publish or Perish software with Google Scholar as a database. This study used systematic data to reveal competition contributes to banking performance measured by the size of the company's market forces can be measured using the Lerner Index, Herfindahl-Hirschman Index, or through structural behavioral performance hypotheses (SCP). Researchers typically use concentration ratio, market share or Herfindahl - Hirschman Index (HHI). Using the concentration of bank deposits as a measure of traditional competition. More specifically, total bank deposits by the three largest banks in a country are divided by the total deposits in the country. As. HHI is the sum of the square market share of each bank in a country.